LEMARI PENYIMPANAN LABTOP DENGAN PENGATUR SUHU DAN KELEMBABAN TERPROGRAM - Achmad Fitro , Aji Wahyu Susanto, Rudianto , Arief Budijanto , (JBT (JURNAL BISNIS dan TEKNOLOGI), 2024)
Laptop storage cabinet with temperature and humidity sensor is a storage that can prevent the growth of fungus that can damage the equipment stored in it including laptops. This storage cabinet uses DHT11 sensor as a temperature and humidity sensor and uses Arduino Uno R3 microcontroller, in addition inside the storage cabinet there is a halogen lamp that functions as a heater if the humidity in it is high and the temperature decreases. The purpose of this study is to reduce waste or laptop waste that is damaged due to fungus growing on important components in it.